KEDUDUKAN AHLI WARIS TERHADAP HARTA PENINGGALAN DALAM PERKAWINAN DENGAN PERJANJIAN PISAH HARTA (PUTUSAN MA NOMOR 804/PK/PDT/2009) - RIZKA YUSTIARIDINIA (PREMISE LAW JURNAL, 2017)
Property separation agreement is dine to separate joint property. Its consequence is that joint property in a marriage there are only a husband’s personal property and a wife’s personal property. Property separation agreement will influence the distribution of inheritance to heir(s) when one of the married couple dies. The Supreme Court’s Ruling No. 804/Pk/Pdt/2009, there is a case when the husband loses his right to be the heir of his wife because they have made property separation agreement. The research problems are how about the legal consequence of property separation agreement in a marriage, how about the legal protection for an heir on the inheritance of one of them as the result of property separation agreement, and the judge’s legal consideration in the Supreme Court’s Ruling No. 804/Pk/Pdt/2009. Keywords: Property Separation Agreement, Heir, Inheritance